Effects of Internal Service Quality on Work Engagement: A Case Study of Hotel Soaltee Crowne Plaza - Shakya, Eveeta; Tamang, Puja (Journal of Business and Social Sciences Research, 2020)
This study examined the Service Quality (SERVQUAL) model with the Internal Service Quality (ISQ) dimensions such as tangibles, reliability, responsiveness, assurance and empathy that impact on employee work engagement. This research work was conducted in Hotel Soaltee Crowne Plaza (SCP), one of the 5-star deluxe hotels of Nepal. The study has adopted an inferential research design to meet the study objectives regarding the impact of independent variables on work engagement of SCP Hotel. A structured questionnaire was distributed to 126 sample respondents out of a total of 503 employees of SCP hotel. The study reveals a significant relationship of work engagement with empathy and not with rest of the independent variables. Based on the findings it is recommended that employees should be taken good care of, and employers should be well aware of the employees’ emotional level since empathy has shown a highly significant relationship with work engagement. Study results have scope of future reference whereby implementing SERVQUAL dimensions for employee work engagement and reduction in employee turnover and improved.